The “Two Camps” Competition: the 1894 Hong Kong Plague in Two English Medical Journals - Fan, Ka-wai (Medicina Historica, 2022)
Scholars have paid much attention to discussing who was first to discover the plague bacillus in 1894, Kitasato Shibasaburō or Alexandre Yersin. This paper, using publications as they appeared chronologically in The Lancet and the British Medical Journal (BMJ), demonstrates that two camps competed with each other to report the news and findings, as well as to express their standpoints. One camp included Shibasaburō Kitasato, James Lowson and The Lancet, while the other included Alexandre Yersin, James Centlie and the BMJ. This paper concludes that when discussing who was first to discover the plague bacillus, the historical facts should be made clear, especially the “two camps” competition. The roles and publications of James Lowson and James Cantlie in the controversial debate on the discovery of the plague bacillus should not be neglected.